TINDAK TUTUR PERSUASIF PEDAGANG KAKI LIMA DI PASAR KAGET GELORA HAJI AGUS SALIM PADANG - Ridho Kurniawan; Yuliatri Novita (LP3M Universitas Muhammadiyah Muara Bungo, 2020)
The aim of the analysisis to find the form and function of persuasive speech act whic used by street vendor in weekend sesonal in Agus Salim stadion. The result of analysis which taken from 19 different places shows that there are 39 data found as the form of persuasive speech acts. According to the data, the writer finds 3 types of persuasive speech acts. They are 25 assertive, 13 of directive, and 1 commisive. Beside that , there are also 6 persuasive speech function which classified as 18 persuasion, 11 suggestion, 7 enticement, 1 invitation, 1appeal, and 1 request. The most widely used form of persuasive speech is assertive and the most widely used speech function is the persuasion function.